Early readmission and reoperation characteristics of ambulatory hypospadias repair. Issue 6 (December 2018) - Roth, J.D.; Whittam, B.M.; Carroll, A.E.; Szymanski, K.M.; Misseri, R.; Cain, M.P.; Bennett, W.E.
Summary: Introduction and Background: Hypospadias is a common birth defect. It is present in about 34.2 in 10, 000 live births in North America. However, few studies have evaluated the immediate reoperation and readmission rates following elective repair. Objective: This study aimed to define the rates of readmission and reoperation following elective hypospadias repair, to improve pre-operative counseling on risks of the procedure. Study design: The Pediatric Health Information System (PHIS) was interrogated from 2004 to 2015 for all elective hypospadias repairs (ICD-9-CM code 58.45) performed in the ambulatory surgical setting. The following were then determined: age at initial operation, insurance status, race, presence or absence of readmission or reoperation within 30 days, presence of repeat hypospadias repair (same ICD-9 code), and presence or absence of another urethral operation (ICD-9 CM code 58.XX, excluding 58.45). Mixed effects logistic regression were then performed with dependent variables of 30-day repeat encounter, 30-day emergency department (ED) visit, 30-day readmission, or 30-day reoperation; and independent variables of age, race, ethnicity, and insurance status. Results: The study identified 45, 264 hypospadias repairs during 2004–2015 performed in 43 hospitals. Within 30 days of the procedures, 2826 (6.2%) had additional encounters in the ED at the same facilities, and 546 (1.2%) had readmissions. A total of 105 (0.2%) underwent second anesthetic within the first 30 days. With regards to a 30-day repeat encounter, odds of repeat encounter were significantly increased in patients aged <5 years, Black and Asian patients, and those with Medicaid. Of the 4882 repeat encounters, 954 (19.5%) had discharge ICD-9 codes related to the penis, or to postoperative complications in general. Discussion: This study described the epidemiology of clinical events occurring at the same tertiary children's hospital within the first 30 days following more than 45, 000 hypospadias repairs. Limitations included a cohort generated from a single set of ICD-9 codes. Conclusions: Elective hypospadias repair had a low rate of readmission (1.2%) and reoperation (0.2%) within the first 30 days. Patients aged <5 years, of non-white race, Hispanic ethnicity, and on Medicaid had significantly higher odds of 30-day repeat encounters.